Eficácia alimentar e qualidade proteica de misturas de caseína com gelatina em dietas com baixos teores de proteína - BORDIN, Cláudia Cantelli Daud (2012)
Gelatin is widely used in human feed, but has limited protein value. The composition in essential amino acids is quite atypical, since the levels of all the amino acids are below the benchmark of Food and Nutrition Board of the Institute of Medicine of the National Academy of Sciences of USA (FNB/IOM), with the aggravating not contain tryptophan in its composition. This study evaluated the effectiveness of food and the quality of protein mixtures of casein with gelatin (4:1 protein-based), in diets with low protein levels. An experimental study on animal model using 36 wealing male Wistar rats (21 to 23 days of age), divided into six groups of six animals each. The following were fed with diets: C10: 10% protein (casein); C8G2: 10% protein (8% casein; 2% gelatin); C12.5: 12.5% protein (casein); C10G2.5: 12.5% protein (10% casein; 2.5% gelatin); G10: 10% protein (gelatin); AP: protein-free. The duration of the experiment was 28 days for groups C10; C8G2; C12.5 e C10G2.5 and 14 days for groups G10 e AP. The effectiveness of food diets containing mixing casein:gelatin was influenced by the gelatin, according to the Food Conversion Ratio to protein level of 10% (C10 = 3.35 ± 0.19 versus C8G2 = 3.91 ± 0.34) and in supplementation with gelatin (C10 = 3.35 ± 0.19 versus C10G2.5 = 3.86 ± 0.32). The protein effectiveness was reduced in the protein level of 10% (C10 = 2.90 ± 0.17 versus C8G2 = 2.41 ± 0.22), in protein level of 12.5% (C12.5 = 2.32 ± 0.19 versus C10G2.5 = 2.03 ± 0.16) and supplementation with gelatin (C10 = 2.90 ± 0.17 versus C10G2.5 = 2.03 ± 0.16) according PER (Protein Efficiency Ratio). The animals that consumed gelatin (G10) had similar weight loss to the protein-free group. Gelatin in mixtures of casein with gelatin (4:1 protein-based), in diets with low protein content, reduces the effectiveness of food protein of casein.